ANALISIS PENYELESAIAN PEMBIAYAAN MURABAHAH BERMASALAH DI BAITUL MAAL WA TAMWIL BINA SWADAYA DURI KECAMATAN MANDAU KABUPATEN BENGKALIS - Retno Nurul Yaumi; Hayatul Ismi; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
A contract of Bai'al Murabahah is the sale and purchase of goods at the original price with additional agreed benefits. A contract is the same as an agreement, that is, a legal act whereby one or more people commit themselves or bind themselves to one or more people. What was realized was an agreement between the customer as the first party and Baitul Maal wa Tamwil (BMT) Bina Swadaya as the second party engaged in the field of microfinance institutions operating based on sharia principles. This agreement includes a cooperation agreement that is classified as a named agreement. Every agreement made by the parties aims to meet the achievements, but in this agreement what happens is a default. The purpose of writing this thesis, namely: first to find out the factors causing murabahah financing problems in BMT Bina Swadaya Duri Mandau District, Bengkalis Regency, second to find out the completion of murabahah problematic financing effectively. This type of research is sociological juridical research. This research was conducted in Baitul Maal wa Tamwil Bina Swadaya which is located in Duri Mandau District, Bengkalis Regency, the data used are primary data, secondary data and data collection techniques in the form of research with interviews and literature review.From the results of the study it can be concluded that, first, the implementation of the contract between the customer and BMT Bina Swadaya was in good faith since the contract was signed. Over time, there are unfulfilled rights and obligations that lead to defaults made by customers to the BMT. As a result of having one of the contents of the agreement that was not fulfilled by the cooperative. Second, the factors causing defaults in this agreement are the economic conditions of customers who are down, natural disasters experienced by the debtor, and the lack of goodwill customers to repay loans. Third, the legal consequences of debtors who have defaulted in this agreement where the debtor is required to repay the loan or pay for the losses suffered by the creditor, where the creditor suffered material losses. Defaults made by the debtor have a negative impact on financial activities in BMT.Keywords: Murabahah-Default-Baitul Maal wat Tamwil